Light modulation ameliorates expression of circadian genes and disease progression in spinal muscular atrophy mice - Walter, L; Koch, C; Betts, C; Ahlskog, N; Meijboom, K; Van Westering, T; Hazell, G; Bhomra, A; Claus, P; Oster, H; Wood, M; Bowerman, M (Oxford University Press, 2018)
Physiology and behaviour are critically dependent on circadian regulation via a core set of clock genes, dysregulation of which leads to metabolic and sleep disturbances. Metabolic and sleep perturbations occur in spinal muscular atrophy (SMA), a neuromuscular disorder caused by loss of the survival motor neuron (SMN) protein and characterised by motor neuron loss and muscle atrophy. We therefore investigated the expression of circadian rhythm genes in various metabolic tissues and spinal cord of the Taiwanese Smn-/-;SMN2 SMA animal model. We demonstrate a dysregulated expression of the core clock genes (clock, ARNTL/Bmal1, Cry1/2, Per1/2) and clock output genes (Nr1d1 and Dbp) in SMA tissues during disease progression. We also uncover an age- and tissue-dependent diurnal expression of the Smn gene. Importantly, we observe molecular and phenotypic corrections in SMA mice following direct light modulation. Our study identifies for a key relationship between a SMA pathology and peripheral core clock gene dysregulation, highlights the influence of SMN on peripheral circadian regulation and metabolism and has significant implications for the development of peripheral therapeutic approaches and clinical care management of SMA patients.